Lipid Synthesis During Sporulation of Saccharomyces cerevisiae - Henry, Susan A. (1973)
Lipid synthesis was studied in both sporulating (diploid) and nonsporulating (haploid) cells of Saccharomyces cerevisiae. Two phases of lipid synthesis occur in diploid cells transferred to sporulation medium. Phase I, which occurs during the first 12 h of exposure to sporulation medium, was also observed in the haploid strains. Phase II, occurring from the 20th to the 25th h, coincided with the appearance of mature asci and was observed only in the diploid cells. The majority of phospholipid synthesis took place during period I, whereas neutral lipid synthesis occurred during both periods. Phospholipid synthesis was virtually identical in both type and quantity in the sporulating and nonsporulating strains.